Investigation of carbon nanotube growth termination mechanism by in-situ transmission electron microscopy approaches - Kim, Seung Min; Jeong, Seojeong; Kim, Hwan Chul (KOREAN CARBON SOC, 2013)
In this work, we report in-situ observations of changes in catalyst morphology, and of growth termination of individual carbon nanotubes (CNTs), by complete loss of the catalyst particle attached to it. The observations strongly support the growth-termination mechanism of CNT forests or carpets by dynamic morphological evolution of catalyst particles induced by Ostwald ripening, and sub-surface diffusion. We show that in the tip-growth mode, as well as in the base-growth mode, the growth termination of CNT by dissolution of catalyst particles is plausible. This may allow the growth termination mechanism by evolution of catalyst morphology to be applicable to not only CNT forest growth, but also to other growth methods (for example, floating-catalyst chemical vapor deposition), which do not use any supporting layer or substrate beneath a catalyst layer.
Keywords: CHEMICAL-VAPOR-DEPOSITION; EVOLUTION; CATALYST; FORESTS; WATER